Analisis Indeks Kepekaan Lingkungan (IKL) Pesisir Pantai Timur Kabupaten Tanjung Jabung Timur – Provinsi Jambi Terhadap Potensi Tumpahan Minyak (Oil Spill) - Iswandi Eka Putra; Anis Tatik Maryani; Hutwan Syarifuddin (Universitas Jambi, 2018)
Offshore exploration and exploitation are activities that can impact the pollution of coastal area. East Tanjung Jabung coastal area is one of area that is susceptive of oil spill contamination since this area is an underwater pipeline path. Oil spill could damage coastal ecosystem such as mangrove and seagrass which are nutrient source, feeding, spawning and nursery ground for sea organism. The aim of this research is to rank environmental sensitivity index and to map Environmental sensitivity index as a guidance to take steps and handle oil spill through the value of environmental sensitivity index indicator. East Tanjung Jabung coast environmental sensitivity index is categorized high (sensitive – very sensitive). All mud substrate area in division 1,2, and 3 are in maximum sensitivity state, very sensitive.